Chinese Financed Hydropower Projects in Sub-Saharan Africa - Deborah Brautigam; Jyhjong Hwang; Lu Wang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2015)
This policy brief provides an analysis of Chinese practice in financing large—over 50 megawatt (MW)—hydropower projects in Africa between 2000 and 2013. Hydropower energy has benefits as a renewable and local source of power, but there can be significant social and environmental risks. These risks have made international banks and aid agencies reluctant to finance large hydropower projects in recent decades. This brief finds that, since 2000, Chinese construction companies and banks have shown sustained interest in 53 large hydropower projects in Africa. However, contrary to popular belief, there can be significant lags to Chinese finance, and many Chinese financiers require important environmental or social impact studies before starting a project.
Keywords: 330